Chemical composition of rain water over Lucknow in 1980 (MAUSAM, 1982)
The analysis of rain water samples collected during the period June-December 1980 showed that there was no incidence of 'acid rain' over Lucknow. The chemical composition of rain water varied from shower to shower and was mainly of the alkaline earth bicarbonate type. In a few cases relatively high concentrations of NO3 6-8 mg/1 were obtained in rain water samples. Amongst the trace constituents iron was the most predominant (av. 26.5 microgram/1) followed by Zinc, strontium, copper, maganese etc in that order.